Development of rematuration of canine chemically induced hepatic progenitor cells using 3D rocking culture - Kaoruko Kikuchi; Yoko Yamada; Sakurako Neo; Suguru Nitta; Hirotaka Igarashi; Akihide Kamiya; Masaharu Hisasue (Regenerative Therapy)
Introduction: Developing canine hepatocyte culture systems is critical for liver transplantation, toxicity evaluation, and drug metabolism studies. However, maintaining viable and functional hepatocytes in long-term cultures remains challenging. Our prior research demonstrated differentiation of cryopreserved canine hepatocytes into hepatic progenitor cells (cHPCs) using three small-molecule compounds: Y-27632 (ROCK inhibitor), A-83-01 (TGFβ inhibitor), and CHIR99021 (GSK3 inhibitor). Nevertheless, rematuration into functional hepatocytes was not achieved. This study aimed to evaluate the differentiation of progenitor cells into mature hepatocytes, compare two-dimensional (2D) and three-dimensional (3D) culture systems, and determine the advantages of 3D culture. Methods: cHPCs were cultured in 2D cultures with HGF and oncostatin M or in 3D cultures using AggreWell400TM plates to form spheroids, transferred to low-adherent plates, and cultured with shaking. Cells were analyzed for morphology, gene expression, and protein markers using immunocytochemistry. Results: In 2D cultures, rematuration produced cells with wider cytoplasm, multiple nuclei, and a paving stone–like morphology. Spheroids in 3D cultures reached 150 μm in diameter with irregular edges by day 5. Quantitative real-time polymerase chain reaction analysis revealed significant upregulation of liver-specific genes. In 2D cultures, KRT19 expression increased 1.7-fold compared with cHPCs(p < 0.01). In 3D cultures, ALB (63-fold), TAT (9-fold), MRP2 (34-fold), EpCAM (1.6-fold), CYP2E1 (10-fold), and CYP3A12 (56-fold) were all significantly upregulated compared with cHPCs (p < 0.05). Immunohistochemistry showed robust AFP, ALB, and CYP2E1 expression in 3D cultures, with 87.6 % of cells AFP-positive and 100 % CYP2E1-positive compared to 11.4 % and 7.9 % in 2D cultures, respectively. Conclusions: 3D rocking culture markedly enhanced liver-specific gene and protein expression, producing functional liver spheroids. These findings underscore the potential of 3D rocking cultures to create reliable, in vivo–like liver models for research and therapeutic applications.